SOSIALISASI PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DENGAN SENAM ERGONOMIK DI WILAYAH KERJA PUSKESMAS SEI PANCUR BATAM - Sri Muharni; Utari Christya Wardhani (Awal Bros Journal of Community Development, 2020)
Hypertension is a common cardiovascular problem in older adults. High blood pressure will cause damage to blood vessels throughout the body, we can control this damage with pharmacological and non-pharmacological therapies, one of which is ergonomic exercise. Ergonomic exercise is a gymnastic movement combined with breathing techniques. This community service aims to lower blood pressure in the elderly. The benefit of this community service is to help the elderly do ergonomic exercise in non-pharmacological lowering of blood pressure. The expected results from this community service, the elderly in the working area of ​​the Pancur Puskesmas. able to perform ergonomic redemonstrations.